Prevalence of depression and associated factors among HIV/AIDS patients attending antiretroviral therapy clinic at Dessie referral hospital, South Wollo, Ethiopia - Seada Seid; Oumer Abdu; Mebratu Mitiku; Koku Sisay Tamirat (International Journal of Mental Health Systems, 2020)
Abstract Introduction Depression is one of the common mental health disorders and predicted to be the second cause of the global health burden by the year 2020. Depression in HIV patients may lead to poor engagement to their HIV care which may finally result in poor treatment outcomes. Therefore, the aim of this study was to assess the prevalence of depression and associated factors among HIV/AIDS patients on ART at Dessie referral hospital. Methods An institution based cross-sectional study was conducted among 395 HIV positive adult patients on antiretroviral treatment from November to January 2019. The study participants were selected by using the systematic random sampling technique among patients who visited the antiretroviral (ART) clinic in the hospital and standardized Patients Health Questionnaire (PHQ-9) was used to measure depression. Descriptive statistics like percentage, median with interquartile range (IQR) was computed and presented in the form of text and table. Binary logistic regression model was fitted to identify factors associated with depression. An adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to identify factors associated with depression. Result The prevalence of depression was found to be 20% with (95% CI 16.2, 23.8). Age group of 25–34 years (AOR = 6.58, 95% CI 1.11, 38.9), widowed marital status (AOR = 7.05, 95% CI 2.32, 21.38), perceived stigma (AOR = 2.43, 95% CI 1.13, 5.21)], had opportunistic infections [AOR = 4.96, 95% CI (1.05, 23.34)], HIV non-disclosed HIV status (AOR = 6.34, 95% CI 1.34–29.65), poor and fair drug adherence (AOR = 7.1, 95% CI 2.06, 24.44), CD4 count ≤ 200 (AOR = 5.38, 95% CI 2.37–12.23) were factors significantly associated with depression. Conclusion The magnitude of depression was relatively lower than the pooled estimates for Ethiopia. Perceived stigma, younger age, widowed, being symptomatic, fair and poor adherence, recent opportunistic infection, low CD4 count, and HIV status not disclosed were positively associated with depression. This finding suggests the integration of mental health care with antiretroviral therapy and the special emphasis ought to be given for those at higher risk of depression.